Effects of the Pulsed Electromagnetic Fields on Experimental Periodontitis and Estrogen Deficiency - Bernardo, Daniella V. [UNESP] (2022)
Periodontitis is an inflammatory disease resulting from a complex polymicrobial infection that causes tissue destruction in susceptible individuals. Osteoporosis has been associated with greater clinical attachment loss in patients with periodontitis. Experimental studies have shown positive results in the treatment of osteoporosis through pulsed electromagnetic field (PEMF) stimulation. The aim of this study was to evaluate the effects of PEMF in the presence of estrogen deficiency associated with periodontitis, verifying its role in bone metabolism and in the inflammatory response. Sixty rats were divided into four groups: Sham surgery + ligature-induced periodontitis (P); Sham surgery + ligature-induced periodontitis + PEMF therapy (P + PEMF); Ovariectomy surgery + ligature-induced periodontitis (P + OVX); Ovariectomy surgery + ligature-induced periodontitis + PEMF therapy (P + OVX + PEMF). The area of bone loss in the furcation region (BL), connective tissue attachment loss (CTAL) and alveolar bone loss (ABL), BV/TV and BMD were evaluated. In addition to immunohistochemical labelling of RANKL, OPG, and TRAP and the inflammatory response of interleukin (IL)-1b, IL-6, TNF-α, IL-10, and vascular endothelial growth factor. P + OVX showed significant BL in relation to P + PEMF and the greatest CTAL and ABL. P + OVX and P + OVX + PEMF showed a significant reduction in BV/TV (%). P and P + PEMF showed a significantly lesser amount of Tb.Sp (mm) while P + OVX and P + OVX + PEMF showed a lesser of Tb.N. P + PEMF had the greatest BMD. P + OVX presented higher RANKL and lower OPG immunolabeling than other groups. P + PEMF and P + OVX + PEMF showed a reduction on all biomarkers evaluated. The application of PEMF seems to attenuate the effects of bone loss in the presence of periodontitis and ovariectomy. © 2022 Bioelectromagnetics Society.